PERTUMBUHAN MATA TUNAS OKULASI TANAMAN KARET (Hevea brasiliensis) PADA BERBAGAI KONSENTRASI ZPT ATONIK Growth Of Eye Grafting Crop Rubber ( Hevea Brasiliensis) At Various Concentration of ZPT Atonik - Rossy Mirasari (JURNAL AGRIMENT, 2017)
This research aim to to know influence of giving of Atonik in so many concentration to growth of rubber seedgrafting bydm soriyt eye at stadium of stum sleep eye. Concentration the used is Atonik 0,5 ml / water litre ( A1),Atonik 1 ml / water litre ( A2), Atonik 1,5 ml / water litre ( A3), and without usage of Atonik ( A0). While treatmentof base given is same to all rubber seed. Result of research indicate that concentration of Atonik give bestinfluence and differ reality to growth of rubber seed grafting bydm soriyt eye at all of perception parameter, that isbydm soriyt length, amount of bydm soriyt diameter and leaf, compared to treatment of other concentration.